2004
DOI: 10.1016/j.ejcts.2004.01.043
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results and quality of life after surgery for oesophageal achalasia: one surgeon's experience1

Abstract: Objective: To assess the long-term results and health-related quality of life in patients undergoing surgery for oesophageal achalasia. Methods: Thirty-nine patients with achalasia (25 males, mean age 42^13 years) underwent open-Heller myotomy and Dor fundoplication by the same surgeon. Long-term results were assessed by imaging, endoscopy, manometry, pH-metry, and Short Form 36 and Nottingham Health Profile questionnaires whenever applicable. Six patients were at radiological stage I, 20 were at stage II, 2 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 21 publications
0
12
0
3
Order By: Relevance
“…Patient quality of life has been demonstrated to be significantly improved after myotomy in several studies [51][52][53][54], and patient satisfaction rates with surgery have consistently been reported to exceed 80-90% [44,47].…”
Section: Myotomy Outcomesmentioning
confidence: 99%
“…Patient quality of life has been demonstrated to be significantly improved after myotomy in several studies [51][52][53][54], and patient satisfaction rates with surgery have consistently been reported to exceed 80-90% [44,47].…”
Section: Myotomy Outcomesmentioning
confidence: 99%
“…The advantage of a less invasive, safe, and effective surgical option prompts gastroenterologists to choose patients earlier for surgery, because this obviates the need for dilation 44,45…”
Section: Surgerymentioning
confidence: 99%
“…60 Long-term follow-up has shown that dysphagia relapse rates may be as low as 8-10% from 6 to 9 years after surgery. 60,61 However, the advent of minimally invasive surgical techniques to treat achalasia has dramatically altered the management algorithm for many gastroenterologists. The advantage of a less invasive, safe and effective surgery entices many gastroenterologists to send their patients to surgery early after the initial diagnosis of achalasia as this obviates the need for dilatation and the inherent risk of oesophageal perforation.…”
Section: Surgerymentioning
confidence: 99%